Resorcylic Acid Lactones Produced by an Endophytic Penicillium ochrochloron Strain from Kadsura angustifolia - Song, Hong Chuan; Qin, Dan; Liu, Hai Yang; Dong, Jin Yan; You, Chuan; Wang, Yu Meng (Planta Medica, 2020)
Four new β-resorcylic acid lactones, including penochrochlactone A (2), 4-O-desmethyl-aigialomycin B (4), and penochrochlactones C and D (5 and 6), two compounds isolated from a natural source for the first time, 5α, 6β-acetonide-aigialomycin B (1) and penochrochlactone B (3), together with six known compounds, aigialomycin F (7), aigialomycins A, B, and D (8–10), zeaenol (11), and oxozeaenol (12), were isolated from a mycelial solid culture of the endophytic fungus Penicillium ochrochloron SWUKD4.1850 from the medicinal plant Kadsura angustifolia by sequential purification over silica gel, Sephadex LH-20 column chromatography, and preparative HPLC. Their structures were elucidated by extensive spectroscopic analysis and chemical conversions. In addition, all the new compounds were evaluated for their cytotoxic and antibacterial activities in vitro. Penochrochlactone C (5) displayed moderate cytotoxicity against the HeLa tumor cell line with an IC50 value of 9.70 µM. In the antibacterial assays, compounds 4 – 6 exhibited moderate activities against Staphylococcus aureus, Bacillus subtilis, Escherichia coli, and Pseudomonas aeruginosa with MIC values between 9.7 and 32.0 µg/mL.
Keywords: Kadsura angustifolia; Schisandraceae; resorcylic acid lactones; Penicillium ochrochloron; cytotoxity; antibacterial activity